Emergency valve‐in‐valve transcatheter aortic valve implantation for endocarditis degeneration. Issue 3 (30th January 2020) - Fathi, Amir S.; Ali, Jason M.; Mann, Sam; Taghavi, John; Davies, Will R.; Sudarshan, Catherine
Abstract: The use of transcatheter aortic valve implantation (TAVI) in the emergency setting has not been widely reported, and TAVI is generally contraindicated in the context of endocarditis. Here we describe a patient developing acute cardiogenic shock due to prosthetic aortic valve degeneration with free‐flow aortic regurgitation 8 months after receiving treatment for confirmed infective endocarditis. Due to his clinical status, he was deemed unfit for redo surgery, and he underwent salvage valve‐in‐valve (ViV)‐TAVI. The patient made an excellent recovery. Postprocedure he was treated with a 6‐week course of antibiotics, and at 18‐months follow‐up remains very well with no evidence of reinfection. This case may demonstrate that for selected patients with degenerative prosthetic aortic valve disease, despite a history of infective endocarditis, ViV‐TAVI may be considered an alternative to redo surgery in the emergency setting.